Effect of doses of eCG and cloprostenol on oestrus and ovulation induction in North Moroccan goats during the anoestrus season - El Kadili S.; Raes M.; Bister J.; Archa B.; Kirschvinck N.; Chentouf M. (Innovation for sustainability in sheep and goats, 2019)
This study was conducted to evaluate the effectiveness of hormonal protocols with different doses of eCG and cloprostenol in induction and synchronization of oestrus in North Moroccan goats. Thirty-two adult goats were divided into four groups adjusted for age and live weight (values?? )f. Animals were treated for 11 days with an intravaginal sponge impregnated with 20 mg FGA. Two days before sponge removal, all groups received an intramuscular injection of 300 UI (T1 and T2) or 500UI (T3 and T4) of eCG plus 50 μg of cloprostenol for the T2 and T4 groups. Four fertile bucks were used to detect oestrus 12h after sponge removal and blood samples were collected every 2h from 20 to 60h following sponge removal to determine plasma LH concentrations. Oestrus and LH pic responses were similar in all groups (T1, 100%; T2, 87.5%; T3, 100%; T4, 100%). There were no statistically significant differences (P>0.05) between the groups for the onset of oestrus (26.8 ± 9.4 h, 35.6 ± 8.7 h, 21.5 ± 13h and 23.2 ± 12.7 h respectively for T1, T2, T3 and T4 groups) and preovulatory LH surge after sponge removal (36 ± 13.1 h, 37.4 ± 10.4 h, 27.2 ± 13.4h and 28 ± 9.9 h respectively for T1, T2, T3 and T4 groups). The onset of oestrus and preovulatory LH surge were significantly shorter in groups received 500UI eCG, compared to groups received 300UI (22.32 ± 12.5h vs. 30.6 ± 10h and 27.6 ± 11.4h vs. 36.7 ± 11.5h respectively; p<0.05). Dose of cloprostenol did not affect the induction and synchronization of oestrus and preovulatory LH surge (P>0.05). In conclusion, in hormonal protocols of oestrus and ovulation induction in North Moroccan goats, the utilization of 500UI eCG shortened the onset of oestrus and consequently time to inseminate in North Moroccan goats during anoestrus season. However, the protocol of progestagen treatment with 300UI of eCG can provide for a more efficient program of synchronization. With this protocol AI should be performed later estimated at 53h after sponge removal.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)